2014
DOI: 10.1016/j.sjopt.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Nd:YAG membranotomy for preretinal hemorrhage secondary to valsalva retinopathy

Abstract: Nd:YAG membranotomy is a non-invasive, office-based treatment option that may be successfully used to treat premacular hemorrhage secondary to valsalva retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 30 publications
2
36
0
7
Order By: Relevance
“…In the studies those achieved successful drainage of premacular hemorrhage, visual acuity improved within days in most of the patients, the degree of improvement depended on the underlying and pre-existing macular damage [ 9 , 15 , 17 , 18 ]. As in the previous studies [ 10 , 11 , 22 , 23 ], valsalva retinopathy and Terson’s syndrome in this series showed the best results owing to the lack of underlying pathology. Additionally, in this study, a patient with high altitude retinopathy showed good improvement in visual acuity and we had also observed premacular subhyaloid hemorrhage in 2 more patients who had a history of ascension to high altitude.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the studies those achieved successful drainage of premacular hemorrhage, visual acuity improved within days in most of the patients, the degree of improvement depended on the underlying and pre-existing macular damage [ 9 , 15 , 17 , 18 ]. As in the previous studies [ 10 , 11 , 22 , 23 ], valsalva retinopathy and Terson’s syndrome in this series showed the best results owing to the lack of underlying pathology. Additionally, in this study, a patient with high altitude retinopathy showed good improvement in visual acuity and we had also observed premacular subhyaloid hemorrhage in 2 more patients who had a history of ascension to high altitude.…”
Section: Discussionsupporting
confidence: 83%
“…This signifies that the state of blood in the premacular area is important rather than the duration of symptoms. In this study, we did not compare the success of Nd:YAG laser hyaloidotomy with the duration of symptoms as in other series [ 7 , 8 , 10 , 12 , 15 , 22 , 23 ]. In this series hyaloidotomy was successful in 19 eyes(86.4 %) with visual improvement in all successful cases, though a patient with Eales’ disease after drainage of premacular hemorrhage developed tractional retinal detachment at macula at 6 weeks follow up requiring a pars plana vitrectomy with recovery to 6/6.…”
Section: Discussionmentioning
confidence: 96%
“…Haemorrhages less than this size may not provide adequate cushion effect and this could lead to inadvertent retinal damage by the photodisruptive laser 6. If possible, always drain from a region distant enough from the fovea along the inferior border where there is significant haemorrhagic elevation 7. Khadka et al 1 have recently reported an 86% success rate of Nd-YAG laser in management of premacular SHH in a study on 21 eyes with no complications at 6 months follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the current case is the only report of etoposide and ifosfamide associated with anemia and thrombocytopenia resulting in spontaneous sub-ILM hemorrhage. As in the previously cited cases, we considered treatment with vitrectomy versus Nd:YAG membranotomy [ 15 ]. Delaying intervention runs the risk of scar formation in the pocket of hemorrhage and secondary vision loss.…”
Section: Discussionmentioning
confidence: 99%